Analysis of QRIS Implementation in Increasing Digital Payments in Samarinda, East Kalimantan - Zulfariansyah, Muhammad (SAINTEKBU, 2024)
QRIS (Quick Response Code Indonesian Standard) is a national electronic payment standard that aims to facilitate financial transactions via QR codes. However, QRIS implementation in Samarinda still faces various challenges. The purpose of this study is to analyze the challenges of QRIS implementation in Samarinda and find solutions to overcome them. The method used in this research is descriptive qualitative research with a case study approach. Data is collected through in-depth interviews with various related parties, such as merchants, users, and banks as a payment service provider partner. Data collection was also carried out through field observations and documentation. The results of the study show that the main challenges in implementing QRIS in Samarinda are the lack of public knowledge and understanding of QRIS, inadequate infrastructure, and low participation of merchants. The solution to overcome these challenges is to increase outreach and education to the public, strengthen infrastructure and technology support, and provide incentives to merchants to encourage their participation in using QRIS. The conclusion from this research is that the implementation of QRIS in Samarinda requires greater efforts to increase public understanding, strengthen infrastructure, and provide incentives to merchants. In the long term, implementing QRIS can provide many benefits, such as reducing transaction costs, simplifying payments, and increasing payment system efficiency.